Integrating Ghanaian Ethnomathematical Practices into the Teaching of Trigonometry in Senior High Schools - Prince Kusi; Ebenezer Bonyah; Ernest Larbi (Universitas Negeri Surabaya, 2026)
This study explored how Ghanaian ethnomathematical practices can be integrated into the teaching of trigonometry in Senior High Schools (SHSs), focusing on instructional strategies, teachers’ perspectives, and the challenges associated with implementation. A convergent parallel mixed-methods design was employed. Quantitative data were collected from 70 mathematics teachers using structured questionnaires and analysed using one-sample t-tests and effect sizes. Qualitative data were gathered through semi-structured interviews with four purposively selected teachers and analysed thematically, and the two strands were merged in a joint display during interpretation. The findings revealed strong teacher support for ethnomathematical integration, with teachers reporting that local examples, cultural symbols, collaborative activities, local languages, and indigenous tools enhanced students’ understanding, participation, motivation, and confidence (overall M = 4.14, d = 1.46). Despite these benefits, challenges including inadequate professional development (d = 0.83), limited instructional materials (d = 0.80), insufficient time, and weak institutional support hindered implementation (overall M = 3.64, d = 0.48). The integrated analysis showed that the barriers teachers rated most highly were the same structural gaps they elaborated in interview, while learner comprehension was not a significant barrier. The study recommends structured professional development, curriculum support, and the development of culturally relevant instructional resources for effective ethnomathematical teaching in Ghanaian SHSs.